Kesalahan Berbahasa Jurnalistik dalam Surat Kabar Harian Tribun Pekanbaru - Siska Ayunda; Desi Sukenti (UIR Press, 2023)
Errors in Indonesian are still often found in print media such as magazines, tabloids and even in newspapers. The problems studied in this study are (1) How are journalistic language errors in the Tribun Pekanbaru Daily Newspaper. The aim of this research is to describe, analyze, interpret and collect data about journalistic language errors in the daily newspaper Tribun Pekanbaru. The theory used in this research is Anwar's theory of the application of journalistic language which consists of concise, concise, clear, orderly, and interesting. The research approach used in this research is content analysis. The research method used in this research is descriptive qualitative. The data analysis technique used in this study is an interactive model. The results of this study prove that there are still frequent errors in the writing of news information in the daily newspaper Tribun Pekanbaru during the period November to December 2021 as many as (27) errors, namely errors seen from the concise principle of (4) data, clear principles of (( 3) data, orderly principles of (12) data, brief principles of (6) data, and interesting principles of (2) data.